Two-stage frequency compensation for Doppler shift on BPSK transceiver with LDPC codes for free-space optical communication systems - Meng, Jiacheng; Wei, Tingting; Wang, Yufei; Bai, Zhaofeng; Wu, Junxia; Gao, Duorui; Xie, Zhuang; Zheng, Yunqiang; Nie, Wenchao; Wei, Sentao; Wang, Wei; Xie, Xiaoping (Frontiers in Physics, 2023)
The deployment of low earth orbits is seen as a promising way of enlarging data capacities as well as high data rates. Catering to these interests, optical communication presents possible ways of larger bandwidth than microwave communication. The current generation of mainstream communication systems are classified as coherent systems and incoherent systems, and in particular, coherent systems have received more attention owing to their high receiving sensitivity. This study investigates a digital coherent transceiver, based on BPSK technology. As coherent demodulation will be affected by considering the Doppler shift effect in digital demodulation, Doppler shift of ±GHz can be compensated by adopting a two-stage frequency offset compensation. Moreover, by leveraging a fast filtering algorithm (FFA), a considerable amount of resource consumption is saved in its engineering implementation, and its sensitivity can be significantly enhanced via a high-speed parallel error-correction codec based on LDPC technology.